Localized Laser Heat Treatment on AISI 1045 Steel Using a LPBF Laser - Benjamin Ours; Hammad Ur Rehman; Scott Downard; Timothy Cyders; Brian Wisner (Engineering Reports)
ABSTRACT Laser heat treatment (LHT) can provide local microstructure modification for metallic materials. This study investigates the viability of LHT on AISI 1045 steel using a laser designed for laser powder bed processing (LPBF) with a very small beam diameter compared to existing literature. Energy density models from the literature are analyzed and adapted to improve consistency across varying laser properties, mainly focusing on spot size and laser–material interaction time. Fifteen different laser parameter schematics are evaluated, comparing hardness versus depth relations as well as laser‐affected zone (LAZ) profiles. Through adapting the energy density model, new laser parameters are calculated and demonstrated to produce a valid localized heat treatment.